2004
DOI: 10.1038/sj.jp.7211164
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Response Detects Early Bilirubin Neurotoxicity at Low Indirect Bilirubin Values

Abstract: When sedation, prematurity or other disease processes mask symptoms in the clinically ill newborn, serum bilirubin concentration is monitored as the sole indicator of kernicterus risk. This case emphasizes the value of auditory brainstem responses for the management of indirect hyperbilirubinemia complicated by prematurity, hemolytic anemia, asphyxia, and direct hyperbilirubinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…However, the sensitivity of the auditory system to bilirubin is well documented and several large observational studies have shown a significant association between hyperbilirubinemia and damage to the auditory system [79]. In fact, auditory system damage may occur at TB levels previously thought to be harmless, and may occur in the absence of other signs of classic kernicterus [10]. These auditory effects can range from subtle abnormalities in hearing and speech processing to complete deafness [1114].…”
Section: Introductionmentioning
confidence: 99%
“…However, the sensitivity of the auditory system to bilirubin is well documented and several large observational studies have shown a significant association between hyperbilirubinemia and damage to the auditory system [79]. In fact, auditory system damage may occur at TB levels previously thought to be harmless, and may occur in the absence of other signs of classic kernicterus [10]. These auditory effects can range from subtle abnormalities in hearing and speech processing to complete deafness [1114].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all individuals who did not sur vive in neonatal intensive care units failed ABR screening, and postmortem analysis revealed bilateral hair cell loss in several infants (selectively in IHCs in three of 15), whereas the number of SGNs was not reduced 104 . The auditory system is particularly sensitive to hyper bilirubinaemia 103 . The precise disease mechanisms of bilirubin neurotoxicity are not yet well understood.…”
Section: Acquired Auditory Synaptopathiesmentioning
confidence: 99%
“…Preterm infants are much more likely to have sensori neural hearing loss (1 in 50) than are normalterm neo nates (1 in 1000) 100 . Risk factors for hearing loss include the need for intensive neonatal care 100 , and hyperbili rubinaemia 99,[101][102][103] . Nearly all individuals who did not sur vive in neonatal intensive care units failed ABR screening, and postmortem analysis revealed bilateral hair cell loss in several infants (selectively in IHCs in three of 15), whereas the number of SGNs was not reduced 104 .…”
Section: Acquired Auditory Synaptopathiesmentioning
confidence: 99%
“…[50] found that prolonged latencies of ABR peaks I and V resolved after exchange transfusion. It has been suggested that diagnostic ABR is sensitive to the earliest manifestations of neurotoxicity, and that lowering TB at the time of abnormal ABR may allow only transient toxic neural effects,[8] but there have been no controlled trials to confirm this.…”
Section: Is Bind-induced Auditory Damage Reversible?mentioning
confidence: 99%
“…[47] Auditory pathway damage may occur at total serum/plasma bilirubin (TB) levels which were previously thought to be harmless, and may occur in the absence of other signs of classic kernicterus. [8] In addition, preterm infants may exhibit clinical evidence of kernicterus at normal or marginally elevated TB levels. [9,10] Damage to the auditory system has long-reaching consequences for affected children, as language development is intricately tied to auditory function, and even mild-to-moderate hearing loss can significantly impact a child’s quality of speech acquisition.…”
Section: Introductionmentioning
confidence: 99%